ENHANCING THE INTERNATIONALIZATION OF THE GLOBAL INSURANCE MARKET: CHANGING DRIVERS OF MERGERS AND ACQUISITIONS - D. Rasshyvalov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
One-third of worldwide mergers and acquisitions involving firms from different countries make M&A one of the key drivers of internationalization. Over the past five years insurance cross-border merger and acquisition activities have globally paralleled deep financial crisis.